My giant book of Doraemon 31 rhymes - BPI India (New Delhi : BPI India private Ltd, 2015)
Doraemon Activity Pack is an all-in-one pack for young kids to have a great time at home. With this pack, kids will enjoy hours of coloring and copy coloring and thus improve their coloring skills. The pack also contains puzzle pieces that kids will love to join together to take a complete picture of their favorite Doraemon characters. Not just that, this amazing pack consists of play cards, stickers, crayons and a lot more items that kids can use for numerous fun activities. Time for enthusiastic kids to get ready for endless hours of entertainment with Doraemon and friends!
Location: 2D
Keywords: Rhymes book